2015
DOI: 10.15537/smj.2015.2.10372
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic changes in pregnant women on highly active antiretroviral therapy

Abstract: Objectives:To report on the changes in fibrinolytic activity in human immunodeficiency virus (HIV) infected pregnant women who are undergoing highly active antiretroviral therapy (HAART).Methods:Blood was collected from 50 HIV positive women on HAART (test subjects), and 50 HIV positive women not on HAART (controls). These women were attending the prevention of mother to child clinic (PMTCT) of the University of Benin Teaching Hospital, Benin City, Nigeria from January to June 2014. Standard manual techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Thus, C-suPAR, which lacks the D1 domain, cannot be captured by ATF-HSA. Using this approach, we found that the plasma levels of active suPAR in 20 pregnant women were significantly higher than those in healthy donors, which was consistent with the effects of the overactivation of the fibrinolytic system required for uterine remodeling 136,137 .…”
Section: Detection Of Supar Levels In Plasmasupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, C-suPAR, which lacks the D1 domain, cannot be captured by ATF-HSA. Using this approach, we found that the plasma levels of active suPAR in 20 pregnant women were significantly higher than those in healthy donors, which was consistent with the effects of the overactivation of the fibrinolytic system required for uterine remodeling 136,137 .…”
Section: Detection Of Supar Levels In Plasmasupporting
confidence: 70%
“…Thus, peptides derived from the uPAR-binding regions of uPA have been studied as uPAR antagonists to interrupt uPA-uPAR interactions. Å6, an 8-mer peptide derived from uPA (residues [136][137][138][139][140][141][142][143], demonstrated excellent anticancer and anti-metastatic effects in experimental models and preclinical studies [92][93][94] . Å6 also entered phase I and II clinical trials for cancer treatment [95][96][97] .…”
Section: Upar Antagonists As Anticancer or Anti-inflammatory Agentsmentioning
confidence: 99%
“…(19) The catalytic activity of protein C is enhanced by the vitamin-K-dependent cofactor, deficiency of which distorts the delicate balance between procoagulant and anticoagulant proteins, thus introducing a prothrombotic state. (20) Also in this study, protein S was significantly increased in HIV-positive women on HAART, when compared to those not on HAART and HIV seronegative women. This may be attributed to the direct effect of antiretroviral therapy.…”
Section: Discussionsupporting
confidence: 56%
“…[ 11 12 ] Opportunistic infections, related malignancies, acquired hypercoagulable state, and endothelial dysfunction have been attributed to a lot of these changes in pregnancy and HIV infections. [ 13 14 ] Furthermore, antiretroviral drugs containing protease inhibitors are proposed to cause endothelial dysfunction by their effects on the metabolism of lipid and glucose. [ 15 ] Factors II and V were significantly reduced in HIV-positive pregnant women when compared to HIV-negative pregnant women.…”
Section: Discussionmentioning
confidence: 99%